Identification of aldosterone-induced proteins in the toad's urinary bladder. - Scott, W N (1975)
Aldosterone (the 8,11-hemiacetal 0f 11beta,21-dihydroxy-3,20-dioxo-4-pregnen-18-al) markedly stimulates sodium transport in a number of epithelial tissues. We have attempted to determine whether aldosterone induces the synthesis of specific protein(s) in the course of its action upon the toad urinary bladder. Paired hemibladders were incubated in media containing either [3H]methionine or [35S]methionine; aldosterone in physiologic concentrations was added to one bath and, after incubation, the intact "mitochondria-rich" (MR) and "granular" (G) mucosal cells were isolated. The ratio (3H/35S) was used to identify proteins whose synthesis was induced in the mucosal cells of the steroid-treated bladders. Using exclusion gel chromatography and isoelectric focusing, we identified several aldosterone-induced proteins in the supernatant (105,000 x g) fraction of the MR cell. None was evident in this fraction of the G cell. These proteins have apparent molecular weights ranging from 17,000 to 38,000 and the isoelectric point of the major component is 4.5. Corticosterone (11beta,21-dihydroxy-4-pregnene-3,20-dione) induced the synthesis of proteins in the G cells, but none of these proteins was similar in molecular weight to the aldosterone-induced proteins in the MR cell. Our findings support the hypothesis that aldosterone induces the synthesis of specific proteins and indicate that, in this tissue, these proteins are synthesized by the MR cell.